Mutations in a Partitioning Protein and Altered Chromatin Structure at the Partitioning Locus Prevent Cohesin Recruitment by the Saccharomyces cerevisiae Plasmid and Cause Plasmid Missegregation - Yang, Xian-Mei (American Society for Microbiology, 2004)
The 2μm circle is a highly persistent “selfish” DNA element resident in the Saccharomyces cerevisiae nucleus whose stability approaches that of the chromosomes. The plasmid partitioning system, consisting of two plasmid-encoded proteins, Rep1p and Rep2p, and a cis-acting locus, STB, apparently feeds into the chromosome segregation pathway. The Rep proteins assist the recruitment of the yeast cohesin complex to STB during the S phase, presumably to apportion the replicated plasmid molecules equally to daughter cells. The DNA-protein and protein-protein interactions of the partitioning system, as well as the chromatin organization at STB, are important for cohesin recruitment. Rep1p variants that are incompetent in binding to Rep2p, STB, or both fail to assist the assembly of the cohesin complex at STB and are nonfunctional in plasmid maintenance. Preventing the cohesin-STB association without impeding Rep1p-Rep2p-STB interactions also causes plasmid missegregation. During the yeast cell cycle, the Rep1p and Rep2p proteins are expelled from STB during a short interval between the late G(1) and early S phases. This dissociation and reassociation event ensures that cohesin loading at STB is replication dependent and is coordinated with chromosomal cohesin recruitment. In an rsc2Δ yeast strain lacking a specific chromatin remodeling complex and exhibiting a high degree of plasmid loss, neither Rep1p nor the cohesin complex can be recruited to STB. The phenotypes of the Rep1p mutations and of the rsc2Δ mutant are consistent with the role of cohesin in plasmid partitioning being analogous to that in chromosome partitioning.